Formulasi dan Evaluasi Mutu Fisik Sediaan Masker Gel Peel-Off Ekstrak Biji Pinang (Areca Catechu L.) Sebagai Antioksidan - Asaddah Dwi Mulyani; Mamik Ponco Rahayu; Nur Aini Dewi Purnamasari (Indonesian Journal of Pharmaceutical Education, 2023)
Antioxidants are compounds that can reduce free radicals. Antioxidant compounds in the form of synthetic compounds and natural compounds. One of the plants with antioxidant activity is areca nut (Areca catechu L.). Areca seed extract contains secondary metabolites such as flavonoids, triterpenoids, tannins and has potential antioxidant activity. This study aims to determine the differences in PVA base concentration variations on the physical quality and stability tests of peel-off gel mask preparations and the antioxidant activity of piji areca nut (Areca catechu L.) extract.  This study used areca nut powder which was macerated using 96% ethanol. Areca seed extract is made into a formulation for peel-off gel masks using a PVA base with various concentrations of 10%, 12%, and 14%. Testing the physical quality of the gel peel-off mask preparations included organoleptic tests, homogeneity, pH, viscosity, spreadability, adhesion, dry time, and stability tests. Antioxidant testing of mask preparations was carried out using a UV-Vis spectrophotometer at a wavelength of 516 nm. The research results were analyzed using SPSS on the One Way ANOVA method and independent t test. The results showed that areca seed extract can be formulated into a gel peel-off mask preparation with good physical quality. Formula 2 is a gel peel-off mask preparation which has good physical quality. Antioxidant activity in formula 2 has an IC50 value of 71.789 ppm which is a strong antioxidant.